Love in the Time of Victoria: Sexuality and Desire Among Working-Class Men and Women in Nineteenth-Century London - Young, Beverly (Labour / Le Travail, 1998)
The article reviews the book, "Love in the Time of Victoria: Sexuality and Desire Among Working-Class Men and Women in Nineteenth-Century London," by Francoise Barrel-Ducrocq.